Afetos e queixas de memória em pessoas idosas sem comprometimento cognitivo - Tavares, Patricia do Nascimento (Universidade Federal de São Carlos, 2025)
In the normal aging process, a decline in various cognitive functions is observed, with memory being one of these functions that deserves special attention, as it is a common complaint among older people and can compromise their functional capacity and consequently their quality of life. Positive affect has been identified as a protective factor against the risk of developing mental disorders and cognitive impairment in old age. Nationally, few researchers have dedicated themselves to investigating the influence of positive and negative affects on objective and subjective memory performance among older people. Thus, the present study had the general objective of verifying the relationship between subjective memory complaints (SMQ) and objective memory performance in older people without cognitive impairment. Specifically, the influence of affect and mood on performance in memory tasks and their subjective evaluation was investigated. Forty-four individuals, aged 60 years and older, residing in the municipality of São Caetano do Sul, participated in this research. Participants were pre-evaluated to identify the presence of signs of mild cognitive impairment using the Mini-Mental State Examination. To assess objective performance on memory tasks, the subtests of the WAIS-III scale (Arithmetic, Digits Forward, Digits Backward, and Letter-Number Sequencing) were used. To capture individuals' knowledge, perceptions, and feelings about subjective memory, the Memory Complaints Questionnaire (MAC-Q) was used, and to assess mood, the Geriatric Depression Scale (GDS) and the Geriatric Anxiety Inventory (GAI) were used. Positive and negative affect were investigated using the Positive and Negative Affect Scale (PANAS). Data analysis did not show a significant association between subjective memory complaints and objective performance. However, memory complaints were positively related to symptoms of anxiety and depression, with anxiety being the only significant predictor. Analyzing the relationship between sociodemographic and health variables in the subjective perception of memory, three distinct participant profiles were found, with worse subjective memory assessments reported among younger participants, up to 65 years of age, and among older participants, aged 75 and over. These results highlight the moderating role of mood disorders in the subjective perception of memory in aging. Further research with a larger sample size is suggested to allow for the generalization of the data.
Affects and memory complaints in older adults without cognitive impairment
Keywords: Memória; Afetos; Envelhecimento; CIENCIAS HUMANAS::PSICOLOGIA; 3. Saúde e Bem-Estar